Preoperative Biliary Decompression Preceding Pancreaticoduodenectomy With Plastic or Self-Expandable Metallic Stent. (June 2015) - Haapamäki, C.; Seppänen, H.; Udd, M.; Juuti, A.; Halttunen, J.; Kiviluoto, T.; Sirén, J.; Mustonen, H.; Kylänpää, L.
Background and Aims: The rainage (PBD) prior to pancreaticoduodenectomy (PD) is controversial. If PBD is required, large bore self-expandable metallic stents (SEMS) are thought to maintain better drainage and have fewer postoperative complications than plastic stents. The confirming evidence is scarce. The aim of the study was to compare outcomes of surgery in patients who underwent PBD with SEMS or plastic stents deployed at endoscopic retrograde cholangiopancreatography (ERCP). Material and Methods: This is a retrospective study of 366 patients having had PD during 2000–2009. Preceding endoscopic PBD was performed in 191 patients and nine had had percutaneous transhepatic drainage (PTD). At the time of operation, 163 patients had a plastic stent and 28 had SEMS. Due to stent exchanges, 176 plastic stents and 29 SEMS were placed in all. Results and Conclusions: The stent failure rate was 7.4% for plastic stents and 3.4% for SEMS ( p = 0.697). A bilirubin level under 50 µmol/L was reached by 80% of the patients with plastic stents and by 61% of the patients with SEMS ( p = 0.058). A postoperative infection complication and/or a pancreatic fistula was found in 26% while using plastic stents and in 25% using SEMS ( p = 1.000). In unstented patients with biliary obstruction, the bile juice was sterile significantly more often than in endoscopically stented patients (100% vs 1%, p < 0.001). When the stented and unstented patients were compared regarding postoperative infection complications, there was no significant difference between the groups ( p = 0.365). Plastic stents did not differ from SEMS regarding the stent failure rate, bilirubin level decrease, amount of bacteria in the bile juice, or postoperative complications when used for PBD. The significantly higher price of SEMS suggests their use in selected cases only.